Performance of biodiesel production by means of Ultrasonic Transesterification (2021)
Introduction— In recent years, the use of renewable energies and eco-friendly fuels has increased, among which one of the best performance is biodiesel; the paper shows an upgrade in the efficiency and effectiveness laboratory level’s biodiesel obtaining. Objective— Evaluating the production of biodiesel employing ultrasound is presented, leading to improve the response time and efficiency of the reaction, concerning the conventional method using only temperature. Methodology— In the transesterification process, castor oil, methanol, and potassium hydroxide are used, obtaining biodiesel and glycerin. A factorial design with two levels for transit time, mixing temperature, and ultrasound intensity were applied in an instrumented scale reactor to control these variables. Results— In the tests, values close to the reference stoichiometric value of the reaction were obtained. The statistic indicates a normal behavior of data, and identifies it as a factor of incidence in the efficiency of the reaction to the intensity of the ultrasound, concerning the response time of the reaction, the mixing temperature and the intensity of ultrasound. Conclusions— The efficiency of the reaction concerning the studied factors, it only depends on the ultrasound obtaining up to 95.7% of the stoichiometric value; and the response time of the reaction depends on the temperature and ultrasound, obtaining times of formation of product four times faster.